THE ROLE OF A WOMAN-MOUNTAINEER IN THE IMAMATE STATE - Tilakaeva, H O (History, Archeology and Ethnography of the Caucasus, 2016)
The article is devoted to the study of a relevant and very interesting problem today as role of the woman mountaineer in times epoch of national liberation struggle of the mountaineers under Imam Shamil’s direction in Imamate state. At present, the problem is underinvestigated. There are recollections of eyewitnesses and participants of these events